Високоточний плівковий витратомір - Теплюх, З.; Парнета, О. (Видавництво Національного університету “Львівська політехніка”, 2004)
In this work the principles of construction precision and reliable gas film flowmeter with expanded measurement range are designed.
Keywords: 681.121.852.08